2006
DOI: 10.1530/rep-06-0055
|View full text |Cite
|
Sign up to set email alerts
|

Interactive effects of granulosa cell apoptosis, follicle size, cumulus–oocyte complex morphology, and cumulus expansion on the developmental competence of goat oocytes: a study using the well-in-drop culture system

Abstract: Interactive effects of granulosa cell apoptosis, follicle size, cumulus-oocyte complex morphology, and cumulus expansion on the developmental competence of goat oocytes: a study using the well-in-drop culture system Zheng-Bin Han, Guo-Cheng Lan, Yan-Guang Wu, Dong Han, Wei-Guo Feng, Jun-Zuo Wang and Jing-He Tan AbstractUsing a well-in-drop (WID) oocyte/embryo culture system that allows identification of follicular origin, we have investigated the effects of granulosa cells (GCs) apoptosis, follicle size, cumu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
38
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(45 citation statements)
references
References 51 publications
5
38
1
1
Order By: Relevance
“…These data are also in agreement with the results reported by other groups, confirming the positive influence of larger follicular diameter on development at the blastocyst stage that has been championed by many authors (HAN et al, 2006;LEQUARRE et al, 2005;LONERGAN et al, 1999). Despite the several important reproductive differences between taurus and indicus, it seems that this current point is quite similar.…”
Section: Discussionsupporting
confidence: 92%
“…These data are also in agreement with the results reported by other groups, confirming the positive influence of larger follicular diameter on development at the blastocyst stage that has been championed by many authors (HAN et al, 2006;LEQUARRE et al, 2005;LONERGAN et al, 1999). Despite the several important reproductive differences between taurus and indicus, it seems that this current point is quite similar.…”
Section: Discussionsupporting
confidence: 92%
“…Many studies have suggested that a low level of atresia tends to improve the in vitro competence of oocytes [23,[64][65][66]. Our recent work showed that early atresia was beneficial to both competent and incompetent goat oocytes [67].…”
Section: Discussionmentioning
confidence: 79%
“…In addition, oocytes matured in vivo are more competent than those matured in vitro (Blondin et al, 2002;Rizos et al, 2002). Moreover, it has been shown that developmental competence may differ signifi cantly among oocytes with the same COC morphology and follicle size and the same extent of cumulus expansion (Han et al, 2006). These observations suggest that the developmental potential of an oocyte is determined by multifactorial interactions (Han et al, 2006).…”
Section: Introductionmentioning
confidence: 99%